Teaching History in the Boletim do Historiador da ANPUH-SP (1990-2002) - Giavara, Ana Paula; Barreiro, Iraíde Marques de Freitas [UNESP] (Revista Historia Hoje, 2022)
Throughout its trajectory, the Associação Nacional de História (ANPUH) and its Regional Nuclei have established themselves as spaces for dialogue on topics relevant to History professionals, professors and teachers. In the state of São Paulo, these debates take place in seminars and research groups, in biannual meetings, periodicals, as well as in the Boletim do Historiador, informative periodical publication by ANPUH-São Paulo, whose circulation took place between 1990 and 2002. Based on this perception, this article aims to present the way in which the Boletim do Historiador was constituted as a space for reflections and political positioning of the ANPUH community on History as a school subject. In addition to evidencing the productivity and commitment of ANPUH-SP with issues relevant to education, this investigation also makes it possible to understand movements and tensions that impacted the discipline along the described time period.
O ensino de História no Boletim do Historiador da ANPUH-SP (1990-2002)
Keywords: Associação Nacional de História Seção São Paulo (ANPUH-SP); Boletim do Historiador; History teaching